2012
DOI: 10.1186/1476-511x-11-153
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in lipoprotein-associated phospholipase A2 levels during acute coronary syndrome and its relationship to standard biomarkers

Abstract: BackgroundLipoprotein-associated phospholipase A2 (Lp-PLA2) probably plays an important role in the development of acute coronary syndrome (ACS); elevated levels of Lp-PLA2 are associated with a poorer prognosis in patients with ischemic heart disease. Alterations of Lp-PLA2 levels during ACS and its relationship to standard biomarkers are, however, unclear.FindingsFifty-one consecutive ACS patients were enrolled in the study. All were managed with early invasive strategy and according to the current guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Firstly, most of studies were based on single measurement of circulating Lp-PLA2, [ 7 12 , 21 ] and only a few observed the change of Lp-PLA2 over time. [ 16 , 17 ] Ostadal et al [ 16 ] found that serum levels of Lp-PLA2 were significantly elevated in patients with ACS, but decreased within the first 24 hours after admission and subsequently remained stable. In our study, dynamic changes in Lp-PLA2 were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, most of studies were based on single measurement of circulating Lp-PLA2, [ 7 12 , 21 ] and only a few observed the change of Lp-PLA2 over time. [ 16 , 17 ] Ostadal et al [ 16 ] found that serum levels of Lp-PLA2 were significantly elevated in patients with ACS, but decreased within the first 24 hours after admission and subsequently remained stable. In our study, dynamic changes in Lp-PLA2 were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies demonstrated that the Lp-PLA2 concentration was high at first and decreased gradually in patients with ACS over the first 3 days following hospital admission and then remained stable. [ 16 , 17 ] By contrast, Kocak et al found that Lp-PLA2 enzyme activity was significantly lower during the early stage of ACS. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…The data regarding the correlation of Lp-PLA2 changes and hsCRP changes with statin or non-statin therapy obtained in the present study are in line with those in other reports. Ostadal et al reported that no association was observed between the alterations in the levels of Lp-PLA2 and C-reactive protein (CRP; r=0.06, P=0.70) ( 26 ). Another study also reported a lack of correlation between Lp-PLA2 and CRP ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…102 In a recent cohort study, the associations among coronary plaque volume, lipid profiles and circulating Lp-PLA2 levels were analyzed in 40 patients with ACS who had undergone successful percutaneous coronary intervention. Dynamic alterations in Lp-PLA2 have been seen in early stages of acute coronary syndrome (ACS), indirectly supporting the hypothesis of an active role for Lp-PLA2 in the pathogenesis of CHD.…”
Section: Lipoprotein-associated Phospholipase A2mentioning
confidence: 99%